SAFETY MEASURES FOR MINING IN COAL MINES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents safety measures in the conduct of mining operations in coal deposits, which directly affect the technical and economic indicators of mining production and safety requirements.